PENERAPAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN (SAK) PADA USAHA MIKRO KECIL MENENGAH (UMKM) (Studi Kasus pada CV. 7SEVEN di Pulodarat Pecangaan Jepara) - Dwi Maulida, Lelly Faricha; Saptantinah, Dewi; Kristianto, Djoko (Universitas Slamet Riyadi, 2020)
The perpetrators of SMEs generally do not use the standards applicable in the preparation of financial statements. MSME financial statements often use cash basis taken from daily cash mutation sources. The Indonesian Institute of Accountants seeks to contribute to overcome the constraints of MSMEs in the preparation of financial statements by issuing the Financial Accounting Standards of Micro Small and Medium Enterprises (SAK EMKM) and effective from 1 January 2018. SAK EMKM is simple to be implemented easily by MSMEs. This study aims to implement SAK EMKM in the preparation of financial statements of SMEs CV. 7SEVEN Jepara. This research uses qualitative and quantitative approach with case study method. The data used are secondary data sourced from direct observation, and documentation of transaction evidence. The results of the research are the financial statements of CV. 7SEVEN in the form of the statements of financial position, income statement.